Inovasi Pembelajaran: Pemanfaatan Wordwall (Anagram) dalam Meningkatkan Kemampuan Menyimak Bahasa Prancis di SMA Negeri 16 Bandar Lampung - Ikhtiarti, Endang; Kartika, Aulia; Trisna, Indah Nevira (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2024)
This research aims to determine This study was conducted to determine whether the use of the Wordwall website is effective in improving the French listening skills of class XI students of SMAN 16 Bandar Lampung. The subjects of this study were students of class XI-4 as an experimental class consisting of 31 students. This research uses quantitative research with a quasi-experimental method and a One Group Pretest-Posttest Design. The results of the study showed that there was an increase in student learning outcomes, as indicated by an increase in the average pretest score of students from 61.77 to 83.55 in the posttest. Then the t-test value is obtained with a significance value of 0,000 < 0,05, with an N-Gain value of 0,5831, which is included in the category medium. Besides, based on the results of the questionnaire, it was found that the Wordwall website is very interesting to use in learning French, especially for listening skills, and students feel that Wordwall can help increase interest and motivation in learning French listening. However, the Wordwall website still has disadvantages, such as that students need to use headsets or earphones while listening to audio, and they also need a stable network.Kata kunci: Wordwall, Frech, Comprehensio, Media Pembelajaran